Late Pleistocene Uniform Rate of Thrusting Along the Fault's Strike: A Case Study From the Northern Tian Shan Foreland. Issue 4 (12th April 2021) - Pang, Lichen; Lu, Honghua; Wu, Dengyun; Guan, Xue; Zhao, Junxiang; Zheng, Xiangmin; Li, Youli
Abstract: Along‐strike distributions of both the displacement and slip rate of a fault are crucial for understanding its kinematics. This work focuses on along‐strike pattern of the rate of slip on the Huoerguos fault (HF), a thrust fault controlling growth and propagation of the E‐W striking Huoerguos anticline in Fold‐and‐Thrust Belt II in the northern Tian Shan foreland, northwestern China. By using morphological analyses and optically stimulated luminescence (OSL) dating on the terraces, the Late Pleistocene slip rates of the HF have been determined at the north‐flowing Jingou and Sangequan rivers, which are ∼15 km apart and incise deeply the Huoerguos anticline roughly perpendicular to its strike. Our results show that the rate of slip on the HF at the Jingou River is 1.0 + 0.22/−0.15 mm/yr over the past ∼13 kyr. This rate is consistent with the slip rate at the Sangequan River, cutting through the anticline's eastern part, which has been determined between 0.69 + 0.18/−0.11 mm/yr and 1.02 + 0.15/−0.13 mm/yr. This consistence implies that the Late Pleistocene slip rate of the HF is relatively uniform along its strike. Our new data also suggest that the time interval between the age of the topmost terrace alluvium and the basal age of its overlying sediments might not be ignored. Using these two ages as the abandonment age of a given terrace would yield two deformation rates with obvious difference, especially when this terrace has a relatively young abandonment age. Key Points: The Huoerguos fault controls growth of the E‐W striking Huoerguos anticline in the northern Chinese Tian Shan foreland The prominent north‐facing scarps vertically offset the surfaces of terraces of the rivers crossing the anticline The comparable slip rates at Jingou and Sangequan are indicative of uniform distribution of the slip rate along the fault's strike